Design and development of an extendable double-link on two-wheeled mobile robot - Muhammad Taqiuddin bin Abdul Rahman (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The inherent unstable dynamics of two-wheeled mobile robot (TWMR) are characterized by the ability to balance on its two wheels and spin on the spot. A new configuration of TWMR was proposed recently by researcher based on prismatic joint of triple link and balance system has been successfully demonstrated. The configuration is important in many applications including self-balance robot, wheelchair on two-wheels and multilink cranes etc. However, the system takes some distance ahead before stability is achieved over distributed angular angle and extension of the link. This lead to the need for a larger space for the movement of the wheels before it reaches its balance position. Also, the movement of each link will be limited in confine space due to travel constraint. Thus, by introducing Link2 that act as a counterbalance weigh over variation of angle and payload factors, allows flexibility of the system. Hence, the focus of current study are twofold; 1) An integrated modeling and 2) the design controller with COG analysis. The model was developed using two methods. The first method is based on a linearization model mathematically derived using Euler-Lagrange method and represented as a state-space representation. The second method is using commercial Visual Nastran (VN) software. Both methods showed similar instability in open loop response for verification purpose. Then, both linearized and nonlinear equations of motions were tested with different control strategies. The LQR was implemented on the linearized model and the combo controller (PD-Fuzzy and PID controller) was designed to control the nonlinear model of the TWMR. The model has also been successfully substantiated by an extendable double link combo controller of TWMR specifically devised for the purposed of verification. The response predicted from the simulation results is found compliant with the experimental results. The combo controlled TWMR and newly introduced COG analysis fit in the objectives of the study. The study proposed a new procedure for the design and development of future extendable double link TWMR.